Spontaneous Remission in Paroxysmal Nocturnal Hemoglobinuria—Return to Health or Transition Into Malignancy? - Korkama, Eva-Stina; Armstrong, Anna-Elina; Jarva, Hanna; Meri, Seppo (Frontiers in Immunology, 2018)
Paroxysmal nocturnal hemoglobinuria (PNH) is an acquired syndrome characterized by intravascular hemolysis, thrombosis and bone marrow failure. The disease is caused by a mutation in the PIG-A gene that leads to the lack of glycosylphosphatidylinositol-anchored complement regulatory molecules CD55 and CD59 on affected blood cell surfaces. In previous studies spontaneous clinical remissions have been described. The disease manifestations are very heterogeneous, and we wanted to examine if true remissions and disappearance of the clone occur. In a follow-up of a nation-wide cohort of 106 Finnish patients with a PNH clone we found six cases, where the clone disappeared or was clearly diminished. Two of the patients subsequently developed leukemia, while the other four are healthy and in clinical remission. According to our data spontaneous remissions are not as frequent as described earlier. Since the disappearance of the PNH cell clone may indicate either a favorable or a poor outcome - remission or malignancy - careful clinical monitoring in PNH is mandatory. Nevertheless, true remissions occur and further studies are needed to understand the immunological background of this phenomenon and to obtain a better understanding of the natural history of the disease.